2015
DOI: 10.14257/ijunesst.2015.8.11.13
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Safety Attitude and Priority and Progress of Safe Practices of Nurses in Emergency Room

Abstract: The purpose of this study was to examine the relationship between safety attitude and practices of nurses at emergency departments in hospitals. A total of 251 nurses working in the emergency department at 18 hospitals, which have over 300-beds in K-do and C-do (province)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The findings of this study demonstrated significant relationship between the priority given to safety and construction workers' safety-related behavior (safety compliance and safety participation) The finding from this study is consistent with the previous studies (e.g., Hong, 2015;Rundmo & Moen, 2007). For example, Katz-Navon et al (2005) found significant effect on direct relation between safety priority and safety performance.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study demonstrated significant relationship between the priority given to safety and construction workers' safety-related behavior (safety compliance and safety participation) The finding from this study is consistent with the previous studies (e.g., Hong, 2015;Rundmo & Moen, 2007). For example, Katz-Navon et al (2005) found significant effect on direct relation between safety priority and safety performance.…”
Section: Discussionsupporting
confidence: 92%